Você sabe com quem está falando? O direito como discurso e a linguagem jurídica como dominação - Marinho, Marcos José Pestana (2021)
Law and Justice have, for some time, experienced a certain distance from Brazilian society. The refocusing of the legal language (verbal and non-verbal) has been segregating and hindering access to justice, as provided for in our Constitution, thus injuring fundamental rights and guarantees added by the original constituent to Brazilian citizens. Essentially, it is attributed to the "juridiquês" such complications as there is, incredible as it seems, even today, the understanding that the legal language must correspond to a scientific language, more solemn and far-fetched. This situation also makes access to justice more expensive and discredits the Judiciary. However, supported by doctrinal and jurisprudential research, through a socio-philosophical, semiotic approach, the present work analyzes and proposes possible solutions so that language and legal discourse are intelligible, ensuring effective access to justice for Brazilian citizens. What is sought is to broaden the perspectives of the Theme, since it is an individual, constitutional guarantee, inherent to each and every human being, for the exercise and defense of their rights, not only limited to the free access hanging to the Judiciary.